Comparison between modified Allen's test and Barbeau test for the assessment of hands' collateral circulation before arterial puncture among critically ill patients - Ahmed Mohamed Zarea; Nadia Taha Ahmed; Suad Elsayed Abdelmotalb Elsaman (Elsevier, 2021)
Background: Continuous monitoring of critically ill patients requires an important procedure as arterial puncture. The first site of choice for arterial puncture is radial artery. To minimize the risk of ischemic damage to the hands as a radial artery puncture complication, many experts suggest confirming adequate collateral circulation before puncture. Assessment of hands' collateral circulation can be done by modified Allen's test (MAT) and Barbeau test (BT). Aim: To compare between MAT and BT for the assessment of hands' collateral circulation before arterial puncture among critically ill patients. Study design: A descriptive research design was used. Method: The study was conducted at three general intensive care units at university hospital, Egypt. Subjects: A convenience sample of 100 newly admitted patients on the first day and aged from 18 to 60 years old was included. Exclusion criteria were patients with unstable hemodynamics, surgery or burn in upper limbs and arteriovenous shunt. Tool: "Hands' collateral circulation assessment" was used. MAT and BT were done once by the same researcher for all patients. Results: The studied patients showed that 70% had a positive MAT, and 84 % had a positive BT with significant difference between the results of the two tests (p = 0.009). Higher percentages of the patients with a positive BT had normal heart rate (58%), mean arterial blood pressure (58%), body temperature (34%), peripheral pulse (50%), capillary refill time (73%) and warm skin (54%). Conclusion: BT can predict and is more sensitive than MAT in assessing hands' collateral circulation before arterial puncture.